2021
DOI: 10.2217/imt-2020-0296
|View full text |Cite
|
Sign up to set email alerts
|

GO-BEYOND: A Real-World Study of Persistence of Golimumab in Patients with Axial Spondyloarthritis and Rheumatoid Arthritis in Turkey

Abstract: Aim: To evaluate the retention rate of golimumab (GLM) in patients with rheumatoid arthritis (RA) and axial spondyloarthritis (ax-SpA). Materials & methods: Patients had received/were receiving GLM as their first or second biological drug for at least 3 months. We recorded demographic and clinical data, data on drug continuation and disease activity. Patients were classified as biologic-naive and biologic-experienced. Results: The study included 60 RA and 269 ax-SpA patients. At month 24, the retention rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 31 publications
6
9
2
Order By: Relevance
“…This real-life prospective study specifically focused on the effectiveness of GLM in a subgroup of patients who are not normally included in clinical trials, and our findings reveal that in patients with spondyloarthropathies (axSpA and PsA) as well as RA, who need to discontinue their first anti-TNF drug, the decision to switch to GLM can be considered a suitable therapeutic choice. These findings are in agreement with results reported in other recent real-life studies [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This real-life prospective study specifically focused on the effectiveness of GLM in a subgroup of patients who are not normally included in clinical trials, and our findings reveal that in patients with spondyloarthropathies (axSpA and PsA) as well as RA, who need to discontinue their first anti-TNF drug, the decision to switch to GLM can be considered a suitable therapeutic choice. These findings are in agreement with results reported in other recent real-life studies [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our cohort, which shares similar clinical characteristics with the Spanish study in terms of disease duration, comorbidities and concomitant medication, we observed a similar reduction in DAS28-CRP by 3 months in PsA patients (3.8 ± 0.99 at baseline to 2.8 ± 1.1; p < 0.0001) as well as a decrease in BASDAI in axSpA patients (6.02 ± 2.09 at baseline to 4.9 ± 2.2; p < 0.001), although baseline disease activity was higher in our axSpA population. Patients with RA were not included in the study by Alegre-Sancho et al; however, a similar study (in terms of design and patient characteristics) undertaken in Turkey (GO-BEYOND Turkey) did include RA patients [ 22 ]. Akar et al evaluated persistence and changes in disease activity measures over 2 years in 60 RA and 269 axSpA patients after GLM treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL by EQ-5D-5L Domain (% patients with some problems) 1.18) and BASDAI (4.3 vs. 1.6). 9 The smaller improvement observed in the present study may be due to older age of axSpA patients (51 vs. 40 years) and higher CRP levels, and ASDAS and BASDAI scores at baseline. 9 Results from the Italian GISEA registry also corroborate with our findings.…”
Section: Plain Language Summarycontrasting
confidence: 64%
“…9 The smaller improvement observed in the present study may be due to older age of axSpA patients (51 vs. 40 years) and higher CRP levels, and ASDAS and BASDAI scores at baseline. 9 Results from the Italian GISEA registry also corroborate with our findings. 13 A similar reduction in DAS28 (from 4.9 ± 1.2 at baseline to 3.1 ± 1.2 at 12 months) in the subgroup of RA patients who were inadequate responders to one biologic (N = 94) was observed.…”
Section: Plain Language Summarycontrasting
confidence: 64%